PENGARUH LAYANAN KONSELING INDIVIDU TERHADAP PENYESUAIAN DIRI SISWA DI SMAN 2 PRINGGARATA - Junaidi Zultoni; Farida Herna Astuti (Jurnal Paedagogy, 2016)
The purpose of this study was to determine the effect of individual counseling services on the adjustment of class XI students at SMAN 2 Pringgarata. This research method using experimental methods. The sampling technique used in this study was the Quota Purposive Sampling technique. The data collection method used was the questionnaire method as the main method, while the documentation, interviews and observation were complementary methods. To analyze the data using the t-test formula. The results of data analysis are 5,319 and the t value in the table at the 5% significance level with N = 8 is 1,860, this indicates that t is greater than the t table value (5,319> 1,860), which means that Ho is rejected which reads: None The Effect of Individual Counseling Services on the Adjustment of Class XI Students at SMAN 2 Pringgarata, Central Lombok Regency, 2015/2016 Academic Year, and Ha was accepted which reads: There is an Effect of Individual Counseling Services on the Adjustment of Class XI Students at SMAN 2 Pringgarata